Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\frac{9}{2}-\frac{5}{2}\right)-\frac{3}{4}=\frac{4}{2}-\frac{3}{4}=\frac{8}{4}-\frac{3}{4}=\frac{5}{4}\)\(\frac{5}{4}\)
\(\frac{9}{2}-\left(\frac{5}{2}+\frac{3}{4}\right)=\frac{9}{2}-\left(\frac{10}{4}+\frac{3}{4}\right)=\frac{9}{2}-\frac{13}{4}=\frac{18}{4}-\frac{13}{4}=\frac{5}{4}\)
Vậy : \(\left(\frac{9}{2}-\frac{5}{2}\right)-\frac{3}{4}=\frac{9}{2}-\left(\frac{5}{2}+\frac{3}{4}\right)\)
tk mk nha
a] 4/12 ; 5/12 ; 11/2 ; 1/4
b] 1 ; 9/12; 12/5 ; 11/3
c] 8/21; 6/11;8/7
d] 2/3 ;2/7 15/2
a]1/3 5/12 11/2 1/4
b]1 3/4 12/5 33/9
c]8/21 6/11 8/7
d]2/3 2/7 15/2
\(\frac{7}{9}+\frac{9}{10}=\frac{70}{90}+\frac{81}{90}=\frac{70+81}{90}=\frac{151}{90}\)
\(1\frac{1}{10}-\frac{3}{4}=\frac{11}{10}-\frac{3}{4}=\frac{22}{20}-\frac{15}{20}=\frac{22-15}{20}=\frac{7}{20}\)
\(2\frac{1}{4}\)x\(3\frac{2}{5}\)=\(\frac{9}{4}\)x\(\frac{17}{5}=\)\(\frac{9x17}{4x5}=\frac{153}{20}\)
\(\frac{2}{5}:\frac{7}{9}=\frac{2}{5}\)x\(\frac{9}{7}=\frac{2x9}{5x7}=\frac{18}{35}\)
Vì 9/2=2+1/2
Nên 9/2> 2